Pengaruh Pemasangan Kapasitor Shunt Terhadap Konsumsi Daya Aktif Instalasi Listrik - Winasis Winasis; Azis Wisnu Widhi Nugraha (Dinamika Rekayasa, 2007)
The application of shunt capacitor is an alternative solution in improving power factor on electrical installations, so the use of electric energy become more efficient. Here we hope that capacitor will give both technical and economical benefit from decreasing power consumption and electric bill. Contributions of installing shunt capacitor to active power consumption on residential installation, which one of electrical bill has been studied.Based on experimental using 2-14 F capacitors on installation model with inductive load show that shunt capacitors decrease total apparent power (VA) up to 58% dependent of its original power factor, but increase active power consumption (up to10 W). From this, installing shunt capacitors will increase cost of kWh that consumer must paid. Application of shunt capacitors will give any benefits to residential consumer in case releasing power capacity installed.Key word: capacitor, shunt, active power, consumption